Examining How Blockchain Implementation Affects Supply Chain Visibility in Ghana - Dufie, Abena (International Journal of Supply Chain and Logistics, 2024)
Purpose: This article investigate how blockchain technology enhances visibility in supply chains by enabling real-time, transparent data sharing among stakeholders. It explores blockchain's role in reducing information silos and improving traceability. The study aims to inform both industry practitioners and policymakers on blockchain’s benefits and adoption strategies. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Blockchain implementation enhances supply chain visibility by enabling real-time tracking and secure data sharing across stakeholders, reducing fraud and improving traceability. It also helps in verifying product origins, building consumer trust, and streamlining inventory management. However, challenges such as high costs and the need for standardized protocols can limit widespread adoption. Unique Contribution to Theory, Practice and Policy: Transaction cost economics (TCE), resource-based view (RBV) & institutional theory may be used to anchor future studies on the examining how blockchain implementation affects supply chain visibility. For practitioners, the implementation of blockchain technology offers significant potential to improve real-time visibility, data accuracy, and trust within the supply chain. Policymakers should develop standards and regulatory guidelines for blockchain implementation in supply chains to ensure secure and ethical data usage.